1995
DOI: 10.1007/bf00184919
|View full text |Cite
|
Sign up to set email alerts
|

Plantar dislocation of the first metatarsophalangeal joint during lactation

Abstract: Plantar dislocation of the metatarsophalangeal joint of the great toe is a rare injury. We report one example which occurred in a lactating lady following minor trauma, and which was successfully treated by closed manipulation. There was no evidence of major generalised ligamentous laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In contrast to the well-developed body of literature surrounding dorsal dislocation of the first MTP joint, [1][2][3][4][5][6] little is known regarding the pathomechanics and management of dislocation of the first MTP joint in the plantar direction. [7][8][9][10][11] A review of the literature reveals only four documented first MTP joint plantar dislocations. [7][8][9]11 First, Biyani et al 9 reported on a patient with severe open fracture-dislocations of all 5 MTP joints in the plantar direction associated with major trauma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the well-developed body of literature surrounding dorsal dislocation of the first MTP joint, [1][2][3][4][5][6] little is known regarding the pathomechanics and management of dislocation of the first MTP joint in the plantar direction. [7][8][9][10][11] A review of the literature reveals only four documented first MTP joint plantar dislocations. [7][8][9]11 First, Biyani et al 9 reported on a patient with severe open fracture-dislocations of all 5 MTP joints in the plantar direction associated with major trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A review of the literature reveals only four documented first MTP joint plantar dislocations. [7][8][9]11 First, Biyani et al 9 reported on a patient with severe open fracture-dislocations of all 5 MTP joints in the plantar direction associated with major trauma. Second, Sarban et al 11 reported on a 3-month-neglected plantar dislocation of the first MTP joint in a patient with bilateral postaxial polydactyly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations